NaOH-promoted reaction of 1,1-dihaloalkenes and 1H-azoles: synthesis of dihetaryl substituted alkenes - Zhang, Chen; Shi, Yu-Long; Zhang, Li-Yu; Yuan, Dong-Peng; Ban, Meng-Tao; Zheng, Jia-Yao; Liu, Deng-Hui; Guo, Shun-Na; Cui, Dong-Mei (New journal of chemistry, 2018)
An efficient NaOH-promoted synthesis of dihetaryl substituted alkenes from 1,1-dihaloalkenes and 1H-azoles under mild conditions has been developed. The reaction occurred in moderate to good yields and tolerated aliphatic, heterocyclic, and aryl substituted 1,1-dihaloalkenes containing functionalities such as nitriles, ethers, and halogens. Imidazoles and triazoles also afforded the desired products.